Metal-organic framework-derived nanoporous carbon incorporated nanofibers for high-performance triboelectric nanogenerators and self-powered sensors - Rahman, M. Toyabur; Rana, S. M. Sohel; Abu Zahed, M.; Lee, Sanghyun; Yoon, Eui-Sung; Park, Jae Yeong (Elsevier BV, 2022)
Metal-organic frameworks (MOFs), which are highly crystalline materials, possess several intriguing properties but have remained largely unexplored for triboelectric nanogenerators (TENGs). Herein, MOF-derived cobaltbased nanoporous carbon (Co-NPC) incorporated polyvinylidene fluoride (PVDF) composite nanofibers (NFs) are proposed as a highly electronegative tribomaterial for boosting the performance of TENGs in the mechanical energy harvesting applications. Co-NPC, with a high surface area and excellent nanoporosity, greatly improved the electroactive beta-phase formation and the dielectric constant of the PVDF composite NFs. As a result, the surface potential and charge trapping capability of the composite NFs increased by 4 and 9.5 times, respectively, resulting in a significant enhancement of the TENG performance. The as-fabricated Co-NPC/PVDF NF-based TENG (CNP-TENG) showed an excellent power density (19.24 Wm(-2)) and sustainably powered small electronics by harvesting biomechanical energy. The CNP-TENG exhibited excellent output performance at 95% relative humidity (RH) and exhibited stable output for long-term operations (> 60k cycles). Besides energy harvesting, the CNP-TENG was demonstrated as a self-powered pressure sensor with ultra-high sensitivity of 6.39 V/kPa that applied for diverse motion sensing and smart home control system applications. This study successfully introduced MOF-derived nanomaterials to enhance the energy harvesting performance of TENG which paved the way for a new pool of tribomaterials.